2000
DOI: 10.1093/protein/13.7.491
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pore mutations and permeant ion concentration on the spontaneous gating activity of OmpC porin

Abstract: Porins are trimers of beta-barrels that form channels for ions and other hydrophilic solutes in the outer membrane of Gram-negative bacteria. The X-ray structures of OmpF and PhoE show that each monomeric pore is constricted by an extracellular loop that folds into the channel vestibule, a motif that is highly conserved among bacterial porins. Electrostatic calculations have suggested that the distribution of ionizable groups at the constriction zone (or eyelet) may establish an intrinsic transverse electrosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 53 publications
1
36
1
Order By: Relevance
“…The electrophysiological properties of these mutant porins were examined by patch clamp of liposome blisters containing multiple porin channels. Some of the mutant porins displayed a dramatic increase in the closing rate and decrease in open probability relative to wildtype OmpC (17,18). These changes were interpreted to be the result of changes in the flexibility of loop 3 within the barrel, caused by the loss of hydrogen bonds and/or salt bridges between loop 3 and the outer barrel.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The electrophysiological properties of these mutant porins were examined by patch clamp of liposome blisters containing multiple porin channels. Some of the mutant porins displayed a dramatic increase in the closing rate and decrease in open probability relative to wildtype OmpC (17,18). These changes were interpreted to be the result of changes in the flexibility of loop 3 within the barrel, caused by the loss of hydrogen bonds and/or salt bridges between loop 3 and the outer barrel.…”
Section: Discussionmentioning
confidence: 97%
“…The increased channel noise and increased time spent in subconductance states observed in the variant PIBs are reminiscent of the changes in the channel properties of the OmpC porin with mutations designed to disrupt the interaction of loop 3 with the outer barrel (17,18). The electrophysiological properties of these mutant porins were examined by patch clamp of liposome blisters containing multiple porin channels.…”
Section: Discussionmentioning
confidence: 99%
“…The gating of OmpA is associated with breaking and rearrangement of the salt bridges in the center of the barrel (21,23). In the case of the trimeric porin OmpC, it has been proposed that spontaneous gating is related to the positioning or flexibility of loop 3, which folds to form an eyelet (constriction zone) within the pore (24,25). It has been previously suggested that, under acidic conditions, L6 is implicated in the pH-dependent gating of OmpG (7).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the constriction loop in OmpC has been suggested to be important in the gating process. 12,50 Correspondingly, in OpdK the loops L3 or L7 are likely very important for the multiple substates. Hence, we have performed a structural analysis of these loops and compared their flexibility.…”
Section: Simulations Of Ion Conductancementioning
confidence: 99%